The Minang - nomads businesses’ performance: the role of proactive personality, creativity and innovative work behavior - Andri, Gus; Wiwiek Rabiatul Adawiyah,; Purnomo, Ratno; Sholikhah, Zahrotush (Penerbit Universiti Kebangsaan Malaysia, 2020)
Amid the prevalence of particular ethnic supremacy in entrepreneurship, few have looked at the centrality of entrepreneurship in various cultural domains. Authors utilize human capital formation theory to assert that extended family provide a crucial background in the growth of individual business skills and preferences. This study aims at investigating the influence of proactive personality and creativity on small businesses performance owned by the member of Minang business community through the mediating role of the entrepreneurs’ innovative behaviors. The Minang people inherent strong business characters from their ancestors, which is viewed as the enabler of their entrepreneurial success. Data was collected by mean of questionnaire that was distributed to 265 small businesses owners enrolled as the member of Minang business community in Purwokerto Central Java Indonesia. The tool of analysis used was structural equation modeling (SEM). Study results showed that both proactive personality and creativity have positive effect on the Minang Nomads innovative behavior and subsequently on the businesses performance. The study also confirmed the role of innovative behavior as a mediator on the relationship between proactive personalities and creativity.